Prevalence and characteristics of polycystic ovarian syndrome in women attending in outpatient department of obstetrics and gynecology of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh - Fatema, Kaniz; Das, Tripti Rani; Kazal, Rezaul Karim; Mahamood, Sharmeen; Pervin, Hasna Hena; Noor, Farah; Chakma, Bidisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Polycystic ovary syndrome (PCOS) is a heterogenous, multifactorial, complex genetic disorder. Most commonly, it affects the females of reproductive age. This is one of the most widespread diseases across the world and if left untreated, may result in infertility and even uterine cancer. Methods: A cross sectional observation study of 100 PCOS patients was carried out from August 2018 to July 2019 in gynecology out-patient department of Bangabandhu Sheikh Mujib medical university, Dhaka. In this study clinical, biochemical and hormonal profile of these patients were analyzed and correlation was done between clinical features and biochemical and hormonal profile. Results: The prevalence of PCOS was 6.11% in the gynecology out-patient visits and 35.39% among infertile women. The mean age group of the patients was 24.3±5.16 SD. The mean BMI was 24.66±5.34 SD. The mean duration of infertility was 5.17 years. The prevalence of metabolic syndrome in our study was 15.0%. In this study menstrual irregularity was the most common complaint. Spearman’s correlation between various clinical and laboratory parameters showed positive correlation exists between BMI and testosterone (r=0.4824; p<0.0001). Conclusions: The study showed that most of our polycystic ovary syndrome subjects were present with oligomenorrhea. Hirsutism and central obesity were also common presentation. Obese women with PCOS had more severe ovulatory dysfunction and need more attention for their appropriate management.